Ireland : Background Papers. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1995)
This paper considers elements of macroeconomic policy central to Ireland's objective of being among the first countries to enter into European Economic and Monetary Union. The paper analyzes the main determinants of the Irish pound/sterling exchange rate, an issue brought to the fore by the currency turbulence of March 1995, which saw a sterling-inspired decline in the Irish pound against the deutsche mark. It also considers fiscal developments and prospects, highlighting tax reform measures undertaken to accelerate job creation, the growth of spending in recent years, and the medium-term fiscal outlook.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet